97 Efficacy of RestoreX Penile Traction Therapy in Improving Penile Length and Erectile Function Post Prostatectomy. Issue 1 (1st April 2022) - Zganjar, A; Toussi, A; Ziegelmann, M; Yang, D; Manka, M; Kohler, T; Helo, S; Trost, L
ABSTRACT: Introduction: Penile length loss and erectile dysfunction (ED) are common post-prostatectomy. Recent results from a randomized, controlled study (RCT) of RestoreX penile traction therapy (RxPTT) demonstrated preserved erectile function and penile length improvements in men post-prostatectomy. Objective: To report outcomes of the open label phase (6-9 month time point) of the previously noted RCT comparing efficacy of RxPTT to control in men post-prostatectomy. Methods: A randomized, controlled trial (NCT03500419) has been completed of 82 men post-prostatectomy. Men were randomized 1-month post-prostatectomy to no therapy (control, n=27) or RxPTT (n=55) for 5 months. Participants then entered an open label phase for 3 months. Assessments included stretched penile length (corona), standardized (International Index of Erectile Function [IIEF]), and non-standardized questionnaires. Comparisons were performed of men who utilized traction at least 15 minutes daily for both phases to men who were originally control and continued with no treatment (as-treated analysis). Analyses were also performed of men who crossed over from control to >15 min daily (crossover to treatment) and those who were originally in the treatment group and continued with >15 min daily use during the open label phase (ongoing treatment). Results: Of the 82 men enrolled (mean age 58.6), 55 had 6-month, and 42 had 9-month data available to review. Baseline characteristics (IIEF scores, penile length) were similar between cohorts. In the as-treated analysis (no treatment n=7, RxPTT x 8 months n=12, respectively), differences were as noted: IIEF-EFD (-8 vs -0.5, p=0.19), IIEF-OFD (-3 vs -2, p=0.86), IIEF-SD (-1 vs 0.5, p=0.09), IIEF-ISD (-3 vs -0.5, p=0.31), IIEF-OSD (-2 vs 0, p=0.29), penile length (-0.1 vs +1.8 cm, p<0.01), PDE5 use (86% vs 75%, p=0.57), intracavernosal injection use (86% vs 17%, p<0.01). Comparing men who did not use therapy at any time (n=7) to those who crossed over to RxPTT during the open label phase (n=8) demonstrated the following results: IIEF-EFD (-8 vs -6, p=0.49), IIEF-OFD (-3 vs -1, p=0.90), IIEF-SD (-1 vs 0, p=0.55), IIEF-ISD (-3 vs -1, p=0.45), IIEF-OSD (-2 vs -1, p=0.51), penile length (-0.1 vs +0.69 cm, p=0.39). Men who crossed over from RxPTT to no treatment (n=10) had relatively preserved improvements compared to those who continued with RxPTT during the open label phase (n=12) compared to baseline, respectively: IIEF-EFD (0 vs -0.5, p=0.95), IIEF-OFD (-3.5 vs -2, p=0.97), IIEF-SD (0 vs 0.5, p=0.18), IIEF-ISD (0 vs -0.5, p=0.87), IIEF-OSD (0 vs 0, p=0.66), penile length (+1.8 vs +1.8, p=0.99). Conclusions: Although sample size and statistical power are limited, results from the open label phase confirm earlier findings of preserved sexual function and penile length in men treated with RxPTT compared to controls. Men who crossed over from controls to treatment experience benefits, although not as significant as those who were treated beginning at 1 month post-prostatectomy. Men who stopped therapy after 6 months demonstrated stable improvements from baseline, suggesting a preserved effect of RxPTT even after discontinuing use. If validated with external series, these findings would represent a significant advancement in the prevention of sexual dysfunction post-prostatectomy. Disclosure: No